Internet and distributed computing systems : 8th International Conference, IDCS 2015, Windsor, UK, September 2-4, 2015. Proceedings /: 8th International Conference, IDCS 2015, Windsor, UK, September 2-4, 2015. Proceedings. (2015) - Unknown
No abstract available